2010
DOI: 10.1080/19401490903395133
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria decision analysis applied to the design of light-frame wood wall assemblies

Abstract: Designers of light-frame wood wall assemblies should consider several performance criteria simultaneously in addition to minimum requirements set by building codes. Evaluation of various performance characteristics can help select the most suitable configuration for a given project in a given context. In a previous article, we identified appropriate criteria and explored their means of evaluation. Following up, this article integrates the context and the preference of the decision-maker and seeks to obtain a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Rather than using optimization approaches, other researchers resorted to multicriteria decision making (MCDM) methods to compare different architectural designs. For instance, Frenette et al (2010) have demonstrated the feasibility of using MCDM methods in identifying the most suitable design when considering multiple performance criteria.…”
Section: Tablementioning
confidence: 99%
“…Rather than using optimization approaches, other researchers resorted to multicriteria decision making (MCDM) methods to compare different architectural designs. For instance, Frenette et al (2010) have demonstrated the feasibility of using MCDM methods in identifying the most suitable design when considering multiple performance criteria.…”
Section: Tablementioning
confidence: 99%
“…However, the building envelope is a part of the exterior envelope and, therefore, is a truly multifunctional system. The complexity that is created by building envelopes having multiple required features can keep the industry from altering designs and construction methods because a change to one component of the envelope could negatively influence other assembly functions [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Behzadian et al (2010) enumerated 195 papers, from its conception until 2008, where PROMETHEE is applied in environment management (47 papers), business and financial management (25), hydrology and water management (28), chemistry (24), logistics and transportation (19), manufacturing and assembly (19), energy management (17), social (7), design (2), agriculture (2), education (2), sports (1), information technology (1) and medicine (1) . Recently, PROMETHEE has been used in water management (Kodikara et al, 2010;Silva et al, 2010), banking (Doumpos & Zopounidis, 2010), energy management (Ghafghazi et al, 2010;Oberschmidt et al, 2010), manufacturing and assembly (Kwak & Kim, 2009;Saidi Mehrabad & Anvari, 2010;Tuzkaya et al, 2010;Venkata Rao & Patel, 2010;Zhu et al, 2010), logistics and transportation (Lanza & Ude, 2010;Safaei Mohamadabadi et al, 2009;Semaan & Zayed, 2010), quality (Nikolic et al), chemistry (Cornelissen et al, 2009;Ni et al, 2009), maritime commerce (Castillo-Manzano et al, 2009), strategy (Ghazinoory et al, 2009), project management (Halouani et al, 2009), construction (Castillo-Manzano et al, 2009;Frenette et al, 2010), urban development (Juan et al, 2010), location analysis (Luk et al, 2010), environment (Nikolić et al, 2010;Soltanmohammadi et al, 2009;Zhang et al, 2010;Zhang et al, 2009), safety (Ramzan et al, 2009) and e-commerce (Andreopoulou et al, 2009). PROMETHEE method is on the basis of two sorting methods: Promsort (Araz & Ozkarahan, 2007) and FlowSort (Nemery & Lamboray, 2008).…”
Section: Introductionmentioning
confidence: 99%